ANALISIS PERHITUNGAN PENYUSUTAN ASET TETAP MENURUT PSAK 17 DAN UNDANG-UNDANG PAJAK SERTA DAMPAKNYA TERHADAP PENGHASILAN KENA PAJAK PADA PT.WANA ARTA MANUNGGAL - Leroy Lionel Yuhaniar (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2019)
This study aims to determine how the calculation of depreciation of fixed assets inaccordance with IAS 17 and the Law - Tax Law as well as determine the impacton taxable income of both of these calculations. In this study the author usesdescriptive method is a method of analyzing the data which the data are collected,compiled, interpreted, and analyzed so as to produce a complete information andefficient in accordance with the title analysis of calculation of depreciation offixed assets according to IAS 17 and law - tax law and its impact taxable incomeat PT Wana Manunggal Arta